ESTIMASI NILAI RIPITABILITAS BOBOT SAPIH DAN MOST PROBABLE PRODUCING ABILITY KAMBING SABURAI BETINA DI KECAMATAN SUMBEREJO, GISTING, DAN KOTA AGUNG TIMUR KABUPATEN TANGGAMUS - Ibrahim Ikhlas Saputra; Sulastri Sulastri; Muhammad Dima Iqbal Hamdani; Akhmad Dakhlan (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
The research was conducted with the aim of knowing the repeatability estimate and Most Probable Producing Ability (MPPA) value of the weaning weight of female Saburai goats. This research was conducted from July to September 2019 in Gisting, Sumberejo, and East Kota Agung districts, Tanggamus regency, which is the development area for Saburai goat seeds. This research used a survey method. The data used was in the form of primary data obtained from breeders through questionnaires and secondary data, namely in the form of farmer's goat records. The research material consisted of recording of female Saburai goats which had given birth more than twice. The records required in this study included age of dam at delivery, age of kid at weaning (weaning age), kid's birth weight, weaning weight of the kid, type of birth, and sex from 2016 to 2018, and questionnaires for breeders. The results of this study indicated that repeatability estimate of weaning weight of Saburai goat in Gisting, Sumberejo, and East Kota Agung districts were 0.478 (high category), 0.19 (low category) and 0.13 (low category), respectively. The results also indicated that the average MPPA value of weaning weight for Saburai goats in Gisting, Sumberejo, and East Kota Agung districts were 21.91 ± 0.04, 17.91 ± 0.06, and 9.88 ± 0.01, respectively. Keywords: Most probable producing ability, Repeatability estimate, Saburai goat